Association between neighborhood social cohesion, awareness of chronic diseases, and participation in healthy behaviors in a community cohort - Andrew M. Rosenblatt; Deidra C. Crews; Neil R. Powe; Alan B. Zonderman; Michele K. Evans; Delphine S. Tuot (BMC, 2021)
Abstract Background Neighborhood social cohesion (NSC) is the network of relationships as well as the shared values and norms of residents in a neighborhood. Higher NSC has been associated with improved cardiovascular health, largely among Whites but not African Americans. In a bi-racial cohort, we aimed to study the association between NSC and chronic disease awareness and engagement in healthy self-management behaviors, two potential mechanisms by which NSC could impact cardiovascular health outcomes. Methods Using the Healthy Aging in Neighborhoods of Diversity Across the Lifespan Study (HANDLS), we cross-sectionally examined the association between NSC and awareness of three chronic conditions (diabetes, chronic kidney disease (CKD), and hypertension) and engagement in healthy self-management behaviors including physical activity, healthy eating, and cigarette avoidance. Results Study participants (n = 2082) had a mean age of 56.5 years; 38.7% were White and 61.4% African American. Of the participants, 26% had diabetes, 70% had hypertension and 20.2% had CKD. Mean NSC was 3.3 (SD = 0.80) on a scale of 1 (lowest score) to 5 (highest score). There was no significant association between NSC and any chronic disease awareness, overall or by race. However, each higher point in mean NSC score was associated with less cigarette use and healthier eating scores, among Whites (adjusted odds ratio [aOR], 95% confidence interval [CI]: =0.76, 0.61-0.94; beta coefficient [βc]:, 95% CI: 1.75; 0.55-2.97, respectively) but not African Americans (aOR = 0.95, 0.79-1.13; βc: 0.46, − 0.48-1.39, respectively; Pinteraction = 0.08 and 0.06). Among both Whites and African Americans, higher NSC scores were associated with increases in self-reported physical activity (βc: 0.12; 0.08-0.16; Pinteraction = 0.40). Conclusions Community engagement and neighborhood social cohesion may be important targets for promotion of healthy behaviors and cardiovascular disease prevention. More research is needed to understand the different associations of NSC and healthy behaviors by race.